Comparison of short and long co-incubation time of gametes for in vitro fertilization - Pongsuthirak, Pallop (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The short and long co-incubation time of gametes for in vitro fertilization are still debatable issues. This study aims to investigate the effects of short and long co-incubation time of gametes on fertilization, polyspermy, embryonic developmental potential, and clinical outcomes. Methods: Sixty-five patients undergoing IVF treatment were invited to participate in the study between May 2017 and March 2019. Ovarian hyperstimulation was prescribed and oocytes were obtained by trans-vaginal aspiration under ultrasound guidance. Sibling oocytes were randomly allocated to short co-incubation for 4 hours (Group I) in 352 oocytes and long co-incubation for 16-18 hours in 363 oocytes (Group II). Rescue ICSI was carried out if total fertilization failure was documented. Fertilization, embryonic development, and pregnancy outcomes were determined. Results: No significant differences between short and long co-incubation were found in fertilization, polyspermy, cleavage, blastocyst, implantation, clinical pregnancy, and live birth rates. Conclusions: The present study showed that short co-incubation of gametes had no significant difference in fertilization, polyspermy, embryo development, and pregnancy outcomes when compared to long co-incubation. The short co-incubation with early cumulus cell removal and rescue ICSI may have the potential to help a couple who had total fertilization failure.